Modified FOLFOXIRI in Advanced Pancreatic Cancer - Ginocchi, Laura; Vasile, Enrico; Caponi, Sara; Lucchesi, Maurizio; Caparello, Chiara; Lencioni, Monica; Ricci, Sergio; Falcone, Alfredo (JOP. Journal of the Pancreas, 2012)
Context The combination regimen of 5-fluorouracil, folinic acid, oxaliplatin and irinotecan named FOLFIRINOX has been proposed as a new standard of care for metastatic pancreatic cancer patients. However, FOLFIRINOX was associated with high incidence of grade 3 and 4 toxicities (neutropenia in 45.7% of patients with G-CSF use in 42.5% of patients; febrile neutropenia in 5.4%; diarrhea in 12.7%). Our group had developed a very similar schedule in colorectal cancer named FOLFOXIRI which contains no bolus 5-fluorouracil and a slight lower dose of irinotecan. Objective The objective of this study was to prospectively evaluate the tolerability and activity of a modified (m)FOLFOXIRI regimen in metastatic or locally advanced pancreatic cancer patients. Methods The regimen included a lower dose of irinotecan (administered at 150 mg/m2 on day 1 every 14 days) and of infusional 5-fluorouracil (2,800 mg/m2 administered as a 48-hour continuous infusion on days 1 to 3 every 14 days). Folinic acid and oxaliplatin remained unchanged. Results Thirty-nine patients with cytological or histological diagnosis of pancreatic adenocarcinoma have been treated with (m)FOLFOXIRI from August 2010 onwards; 17 had metastatic disease while 22 had locally advanced disease. A total of 260 cycles have been administered so far. The grade 3-4 toxicities reported are: neutropenia in 35.9% of patients, thrombocytopenia 2.6%, diarrhea 5.1%, stomatitis 7.7%, nausea/vomiting 5.1%, fatigue 2.6%, liver toxicity 5.1%, sensory neuropathy 5.1%. No toxic deaths and no febrile neutropenia have been occurred. G-CSF has been used in seven patients (18%). A delay in the administration of chemotherapy was required in 12 patients (31%) and a reduction of doses in 7 cases (18%). Among 30 evaluable patients 11 partial responses (36.7%) and 14 stable disease (46.7%) have been observed. Median progression-free survival (PFS) was 11.5 months and median overall survival (OS) 25.5 months. For metastatic patients only, response rate resulted 33% with a PFS and OS of 8.4 and 14.8 months, respectively. Conclusion The (m)FOLFOXIRI regimen as we used resulted feasible and quite well tolerated and it maintained its good activity in metastatic pancreatic cancer.